2015
DOI: 10.1038/aps.2015.111
|View full text |Cite
|
Sign up to set email alerts
|

Timosaponin derivative YY-23 acts as a non-competitive NMDA receptor antagonist and exerts a rapid antidepressant-like effect in mice

Abstract: Aim: N-methyl-D-aspartic acid (NMDA) receptor modulators have shown promising results as potential antidepressant agents, whereas timosaponins extracted from the Chinese herb Rhizoma Anemarrhenae exhibit antidepressant activities. In the present study we examined whether YY-23, a modified metabolite of timosaponin B-III, could affect NMDA receptors in rat hippocampal neurons in vitro, and evaluated its antidepressant-like effects in stressed mice. Methods: NMDA-induced currents were recorded in acutely dissoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 60 publications
2
10
0
Order By: Relevance
“…Zhang et al had already demonstrated that timosaponin BIII significantly ameliorated depressive effects in rats by regulating inflammatory cytokines, BNDF signaling and synaptic plasticity [29]. We found that YY-21 and YY-23, two modified derivatives of timosaponin BIII, also exhibited antidepressant activity in the animal model [30, 31]. The validated results regarding the antidepressant activities of timosaponin BII and timosaponin BIII were consistent with previous literature reports.…”
Section: Discussionsupporting
confidence: 91%
“…Zhang et al had already demonstrated that timosaponin BIII significantly ameliorated depressive effects in rats by regulating inflammatory cytokines, BNDF signaling and synaptic plasticity [29]. We found that YY-21 and YY-23, two modified derivatives of timosaponin BIII, also exhibited antidepressant activity in the animal model [30, 31]. The validated results regarding the antidepressant activities of timosaponin BII and timosaponin BIII were consistent with previous literature reports.…”
Section: Discussionsupporting
confidence: 91%
“…All the samples exhibit These results indicate that the formation of the small amounts of the anatase after TEA treatment does not accelerate the ineffective decomposition of H 2 O 2 , which is in agreement with that reported in Ref. [62]. However, the catalyst lifetimes of these samples are significantly different.…”
Section: Effect Of the Tea Concentrationsupporting
confidence: 91%
“…Top-down control of the PFC depends on the output neurons within it. Glutamatergic neurotransmissions participate in many brain functions [34] and are key to the output neurons in the PFC; however, it is unknown whether glutamate receptors in the PFC play a role in the effect of MPH on response inhibition.…”
Section: Introductionmentioning
confidence: 99%